Design and development of MIMO antenna for point-to-point application - Rzooki, Mustafa Ghanim (2015)
A Multiple-Input-Multiple-Output (MIMO) Microstrip Patch Antenna 4 ports has been designed and implemented. The proposed antenna consists of four ports and a four Array Microstrip Patch Antenna ground plane extruded on the substrate. The overall size of the proposed substrate is 220 × 220 mm2. The antenna is fabricated on an inexpensive FR4 a dielectric constant ofer = 4.5, loss tangent of tan d=0.019, with thickness of substrate that is 1.6-mm and the thickness of patch is 0.035 mm. The measured results represents that the proposed antenna obtained a reasonable bandwidth from 2.4 GHz that could cover point-topoint application defined by 10-dB return loss. Furthermore, The S-Parameters of antenna are simulated and measured. In this project, design structure of the MIMO antenna four ports and substrate has been employed to broaden the bandwidth. Since MIMO antenna, high gain and directivity can be achieved. Simulation by using CST microwave studio program and measurement on the final prototype antenna were carried out and compared. A MIMO system characteristic evaluation of a four port MIMO antenna operating at 2.4GHz is performed. A four port antenna operating in point-to-point applications is designed, the antenna shows good pattern diversity low correlation coefficient.